2016
DOI: 10.1007/s13277-016-5262-0
|View full text |Cite
|
Sign up to set email alerts
|

Tescalcin expression contributes to invasive and metastatic activity in colorectal cancer

Abstract: We reported previously that tescalcin (TESC) levels were higher in tissue and serum from colorectal cancer (CRC) patients and suggested that TESC was a potential oncotarget in CRC. The aim of this study was to investigate the function of TESC in CRC invasion and metastatic potential. TESC expression was knocked down in CRC cells using small interfering RNA (siRNA). The expression of TESC siRNA reduced cell migration and invasion by inhibiting matrix metalloprotease (MMP) and the epithelial-mesenchymal transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…BAMBI , a transforming growth factor beta ( TGFB ) inhibitor is up-regulated in metastatic carcinomas including colorectal and osteosarcoma ( Fritzmann et al, 2009 ; Zhou et al, 2013 ). Similarly, the expression of PKP2 , a desmosomal adhesions protein has been implicated in glioma and bladder cancer metastasis ( Takahashi et al, 2012 ; Zhang et al, 2017 ) and high expression of Tescalcin, a gene thought to play a role in cell differentiation and implicated in invasive colorectal cancer ( Kang et al, 2016 ). Furthermore, WNT5B , a gene identified within our scRNA-seq Trailblazers has been implicated in cancer aggressiveness in a number of cancer cell lines and tissues ( Harada et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…BAMBI , a transforming growth factor beta ( TGFB ) inhibitor is up-regulated in metastatic carcinomas including colorectal and osteosarcoma ( Fritzmann et al, 2009 ; Zhou et al, 2013 ). Similarly, the expression of PKP2 , a desmosomal adhesions protein has been implicated in glioma and bladder cancer metastasis ( Takahashi et al, 2012 ; Zhang et al, 2017 ) and high expression of Tescalcin, a gene thought to play a role in cell differentiation and implicated in invasive colorectal cancer ( Kang et al, 2016 ). Furthermore, WNT5B , a gene identified within our scRNA-seq Trailblazers has been implicated in cancer aggressiveness in a number of cancer cell lines and tissues ( Harada et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that TESC is involved in the progression of cancer. TESC is overexpressed in colorectal cancer (CRC), but not in normal mucosa and premalignant dysplastic lesions, and its expression contributes to cell proliferation and invasive and metastatic potential 19 , 20 . Furthermore, TESC has been suggested as a potential diagnostic marker for colorectal cancer because serum TESC levels are elevated in patients with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…The final classifier used 25 genes (Supplementary Table 5). Notably, 3 of the most informative genes in the classifier ( TESC 10 , SLC6A8 11 , SPP1 12 ) have been implicated in cancer metastasis and another ( E2F1 ) is an established cell proliferation marker. The cross-validated classifier provided excellent separation between CLD and HCC samples, with a preliminary sensitivity of 85% at a specificity of 95% and with identification of both early and late stage HCC (by Milan criteria) (Figure 2D, Supplementary Figure 2).…”
mentioning
confidence: 99%